Fine-scale plasticity in nest placement can compensate for poor quality junipers as nesting trees for gray vireos - Jonathan Harris (PeerJ Inc., 2021)
Understanding the interactions between behavior and habitat characteristics can have important implications for species of conservation concern. Gray vireos (Vireo vicinior) are one example of a species of conservation concern that is understudied in terms of nest survival probabilities and the habitat characteristics that influence them. Our objective was to determine if habitat features such as juniper density, juniper foliage density, or tree height influence nest survival probabilities, and if gray vireo nest placement can mitigate habitat risks. Based on previous work, we expected daily nest survival probabilities to be associated with nest height and surrounding vegetation. We monitored 89 nests in central New Mexico from 2016–2018 to estimate daily nest survival probabilities. We compared variation in nest placement, nest tree characteristics, and surrounding vegetation between failed and successful nests using logistic exposure models and Akaike Information Criteria. Daily and cumulative nest survival probability were 0.983 (95% CI [0.973–0.989]) and 0.575 (95% CI [0.444–0.702]), respectively. Top models predicting nest survival included a negative interaction between nest-tree foliage density and the distance of the nest from the edge of the nesting tree. This suggests that gray vireos can mitigate risks associated with low nest concealment by nesting closer to the interior of the nesting tree.